2005
DOI: 10.1176/appi.ajp.162.9.1628
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of ADHD Treatments: Findings From the Multimodal Treatment Study of Children With ADHD

Abstract: Objective: Attention deficit hyperactivity disorder (ADHD) is a costly public health problem. To the authors' knowledge, this is the first study on the cost-effectiveness of the major forms of ADHD treatments used in NIMH's Multimodal Treatment Study of Children With ADHD (MTA Study).Method: Five hundred seventy-nine children with ADHD, combined type, ages 7 to 9.9, were assigned to 14 months of medication management, behavioral treatment, both combined, or community care. Services were tallied throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 24 publications
2
104
0
4
Order By: Relevance
“…[5][6][7][8][9][10][11] Treatment options for ADHD include medication management, behavioral treatment, or combination of the two, with medication management being the most cost-effective. 12 Stimulants are an effective first-line treatment option for the majority of ADHD patients, with about 70% of patients responding to treatment in the short term (within 6-10 weeks). 13,14 However, a subset of the patient population treated with stimulants will seek an alternative medication regimen for a variety of reasons, such as lack of improvement, tolerability issues, or the possible negative societal perception of stimulants.…”
Section: Sample Selectionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Treatment options for ADHD include medication management, behavioral treatment, or combination of the two, with medication management being the most cost-effective. 12 Stimulants are an effective first-line treatment option for the majority of ADHD patients, with about 70% of patients responding to treatment in the short term (within 6-10 weeks). 13,14 However, a subset of the patient population treated with stimulants will seek an alternative medication regimen for a variety of reasons, such as lack of improvement, tolerability issues, or the possible negative societal perception of stimulants.…”
Section: Sample Selectionmentioning
confidence: 99%
“…41 The main reasons for our choice of MPH-IR could be summarized as: the high costs of extended-release presentations, the absence of a specific policy for ADHD treatment by the Brazilian authorities, 45 and the high costs of adding combined treatments, as demonstrated by the MTA. 17 Lastly, the MPH-IR prices adopted are exclusively for the Brazilian government, which means they are lower than wholesale prices. To test the difference, an additional analysis for the base case with the highest price on the Brazilian market at the time of writing (I$ 0.56/pill, which represents I$ 50.4/month) was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, countries like the UK, 16 the U.S., 17 Australia, 18 and Spain 19 are largely focusing on economic analysis and health policy for ADHD treatment. To date, a systematic review found 14 studies from different countries on the theme.…”
Section: Introductionmentioning
confidence: 99%
“…Drug treatment, though not as effective as in combination with behavioral treatment, is likely to be more cost effective in treatment of children with ADHD, especially those without co-morbid disorders. 7 Amphetamines have been in use in the treatment of ADHD since last 50 years; and other drugs such as tricyclic antidepressants (imipramine and desipramine), bupropion, pemoline, 3 rd generation antidepressant venlafaxine, selegiline and alpha-2 agonists (clonidine and gaunfacine) also have been tried. 8 Commonly used drugs for treating ADHD in children are stimulants (methylphenidate, amphetamine and methamphetamine), bupropion and atomoxetine (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…7 These agents are last-step alternatives in the management of ADHD. TCAs (imipramine, desipramine, nortriptyline)…”
mentioning
confidence: 99%